Bank competition and financial stability in the Philippines and Thailand - Tomaliwan, Maria Francesca D. (Animo Repository, 2013)
There are two competing theories on the effect of bank competition on bank's financial stability namely the "competition-fragility" and "competition-stability view. The Ce "competition- fragility” view declares bank competition erodes market power, decreases profit margin, and reduces franchise value which encourages banks to take on more risk. On the opposite, "competition-stability” view contends that decrease in competitiveness, determined by market power, increases bank risk. To create opportunities for riskier projects, banks charge higher interest rates to borrowers and thus, resulting to fragility. This paper departs from the existing literature focusing on developed countries by measuring competition on forty banks from the Philippines and Thailand from January 1, 2000 to December 31, 2006. It measures stability through loan risk, overall bank risk and bank capitalization on several market power indicators such as the Lerner Index, HHI deposits and loans. The Generalized Method of Moments estimation is then used to control for possible endogeneity for measures of market power. Empirical evidence reveals that the "competition-fragility” view applies in the Philippines while "competition-stability" view holds for Thailand.